Expansão da cana-de-açúcar e as mudanças no uso da terra no Escritório de desenvolvimento rural (EDR) de Tupã-SP - Fonsêca, Matheus Vinícius Ramalho [UNESP]; Lourenzani, Wagner Luiz [UNESP]; Bernardo, Roberto [UNESP]; Lourenzani, Ana Elisa Bressan Smith [UNESP] (My University, 2015)
The recent dynamics of the sugar cane cultivation in São Paulo State reveals the strong expansion of this culture in the western region. This is explained by investments in expansions and new plants facilities, guided by the increased for ethanol demand in the domestic and international market. Thus, this study aims at analyzing the land use change in the Escritório de Desenvolvimento Rural (EDR) of Tupa, micro region of western of Sao Paulo State, caused by the sugar cane expansion. The method used was the Shift-Share model to decompose the agricultural areas variation and to calculate the replacement of the main activities analyzed. This study revealed that the increasing share of sugar cane cultivation in EDR of Tupa was obtained from incorporation of available lands and from the land replacement of other crops. The peanut crop was the most affected cultivation, because it has lost more area than other agricultural activities.
Expansion of cane sugar and changes in land use in the Rural Development Office (RDO) of Tupa-SP